Art Summer '97 : 66 Estonian Artists : printmaking, painting, sculpture, installation, photo. - Peil, Mirjam (Tallinn : Tallinna Raamatutrükikoda, 1997)
Kurismaa, Kaarel ; Raudoja, Alar ; Elken, Jaan ; Lill, Ivo ; Koha, Eve ; Prääts, Rait ; Riisalu, Toomas ; Eelma, Sirje ; Marks, Ulle ; Ulas, Maria-Kristiina ; Toomik, Jaan ; Arro, Jaak ; Subbi, Olev ; Kolk, Ellen ; Jöekalda, Virge ; Lestberg, Ly ; Nukke, Mall ; Tonts, Annika ; Kurismaa, Mari ; Lapin, Leonhard ; Eelma, Herald ; Puustak, Kaisa ; Järvila, Külliki ; Heam*agi, Inga ; Sarapuu, Lembit ; Büttner, Owe ; Juurak, Anu ; Karmin, Mati ; Kurema, Kadi ; Kask, Jüri ; Kruusing, Agur ; Nagel, Lemming
biog. [5 p.]
Engels & Ests
Art Summer '97 : Estonian Artists, Linnagalerii & Endla teater, Pärnu, 28.6.97 - 16.8.97 ; Raegalerii, Kuressaare, 21.6.97 - 9.8.97 ; Läänemaa Kultuurikeskus, Haapsalu, 5.7.97 - 30.7.97
boek
Keywords: Estland